Developing a Profiling Tool Using a Values Approach to School Renewal. Issue 1 (January 2018) - Brown, Raymond; Heck, Deborah; Pendergast, Donna; Kanasa, Harry; Morgan, Ann
Purpose: The purpose of this article is to outline the evidence-based development of a learning approach to school renewal that employs information from key members of a school community (teachers, parents, students) to promote school-based discussions about school renewal. Setting: The study took place in an independent system of Catholic schools. Schools in this tradition have an enduring history in the development of Catholic education and have partner schools in Australia, New Zealand, Papua New Guinea, India, Africa, Europe, and the Americas. Research Design: The study employed a qualitative sociocultural design focused on generating narratives that could be used to describe the school as a community of practice and the development of a valid and reliable School Renewal Profiling Tool (SRPT) that provides an empirical picture of a school's culture and practice. Data Collection and Analysis: Data collection included school visitations, classroom observations, in-depth interviews, and publicly available school documentation and data gathered from a case study site, a coeducational secondary college located in the center of a metropolitan city. Data collected were subjected to thematic analysis and principal components analysis (PCA). Data gathered from the SRPT items were then presented to the school community in the form of a collated report for feedback and school renewal purposes. Findings: Findings suggest that the SRPT has the potential to capture local ways of knowing and doing as resources to promote organizational school renewal through refecting individual perceptions of participation in collective practice. Conclusions: The research surrounding the development of the SRPT contributes to the field of school renewal in two distinct ways. First, the development of the SRPT offers an approach to school renewal that focuses on the values upon which a school community is based. Second, the SRPT avoids the difficulty of what Fielding (2004) refers to as "speaking about and for others, " where the original thoughts of respondents are couched in the language and values of the researcher.